Gender, work, and satisfaction: a decomposition approach to job satisfaction gaps in Egypt and Tunisia - Mesbah Fathy Sharaf; Abdelhalem Mahmoud Shahen (Frontiers in Sociology, 2025)
IntroductionThis study revisits the paradox of the contented female worker by analyzing gender disparities in job satisfaction in Egypt and Tunisia.MethodsUsing nationally representative labor force survey data, we construct a multidimensional job satisfaction index based on eight dimensions: earnings, job security, nature of work, working hours, work schedule, work environment, commuting distance, and job-qualification match. To explain gender gaps in job satisfaction, we apply the Blinder–Oaxaca decomposition method, both with and without correcting for sample selection bias.ResultsOur results show that conclusions about the existence and direction of the gender gap depend critically on accounting for selection effects. Before correcting for selection bias, women in Egypt report significantly higher job satisfaction than men, while no gender gap is observed in Tunisia—echoing the contented female worker paradox. However, once sample selection is controlled for, the paradox disappears in both countries. In Egypt, the observed gender gap is fully explained by differences in observable characteristics (endowment effect), while in Tunisia, it is largely driven by differences in returns to those characteristics (coefficient effect), highlighting structural inequalities in the labor market.DiscussionTo test the robustness of our results, we also conduct the decomposition using an alternative measure of job satisfaction based on a single overall satisfaction question. The consistency of results across both measures reinforces the validity of our conclusions. Together, these findings caution against relying solely on standard models of job satisfaction and emphasize the importance of considering sample selection and multidimensional outcomes. The study underscores the need for policy interventions that promote fairer working conditions, expand access to employment benefits, and address gender-based disparities in labor markets.